Role of urinary tract infection in development of neonatal pathological unconjugated hyperbilirubinemia - Kumar, Ajay; Batcha, Mohammed Uvaise (Indian Journal of Child Health, 2018)
Introduction: American Academy of Pediatrics recommends investigating for urinary tract infection (UTI) in neonates with conjugated hyperbilirubinemia, but UTI may be associated with unconjugated hyperbilirubinemia also. Objective: The objective of this study was to evaluate the frequency of UTI in initial 4 weeks of life in pathological unconjugated hyperbilirubinemia and to study the effect of treatment of UTI on the course of hyperbilirubinemia in these neonates. Methods: This hospital-based prospective cohort study included 100 consecutive neonates with a gestational age more than or equal to 35 weeks and <42 weeks with unconjugated hyperbilirubinemia in pathological range. Babies were treated with phototherapy (and exchange transfusion), and neonates with UTI were treated with antibiotics also. The primary outcome was the frequency of UTI, confirmed by a positive urine culture and secondary outcomes included positive leukocyte esterase (LE) and nitrite reactions, significant pyuria, and rate of fall of bilirubin levels. Results: Seven neonates had a positive urine culture growth (UTI group) while remaining 93 babies constituted non-UTI group. In the UTI group, six and five babies had positive LE and nitrite reactions, respectively, and four babies had significant pyuria also. Exchange transfusion was done in 23 neonates in the non-UTI group. The median (range) duration of phototherapy in the remaining 70 neonates in the non-UTI group was 39 (15